An Interlaboratory Comparison Study of Regulated and Emerging Mycotoxins Using Liquid Chromatography Mass Spectrometry: Challenges and Future Directions of Routine Multi-Mycotoxin Analysis including Emerging Mycotoxins - Steiner, David; Humpel, Armin; Stamminger, Eleonore; Schoeberl, Anna; Pachschwoell, Gerlinde; Sloboda, Anita; Swoboda, Christy; Rigg, Jolene; Zhang, Dawei; Wang, Yahong; Davis, Joshua; Sulyok, Michael; et al. (Toxins, 2022)
The present interlaboratory comparison study involved nine laboratories located throughout the world that tested for 24 regulated and non-regulated mycotoxins by applying their in-house LC-MS/MS multi-toxin method to 10 individual lots of 4 matrix commodities, including complex chicken and swine feed, soy and corn gluten. In total, more than 6000 data points were collected and analyzed statistically by calculating a consensus value in combination with a target standard deviation following a modified Horwitz equation. The performance of each participant was evaluated by a z-score assessment with a satisfying range of ±2, leading to an overall success rate of 70% for all tested compounds. Equal performance for both regulated and emerging mycotoxins indicates that participating routine laboratories have successfully expanded their analytical portfolio in view of potentially new regulations. In addition, the study design proved to be fit for the purpose of providing future certified reference materials, which surpass current analyte matrix combinations and exceed the typical scope of the regulatory framework.
Keywords: Mycotoxins; internal standard; Glutens; kukuřice setá; method harmonization; gluteny; Chromatography, High Pressure Liquid; vysokoúčinná kapalinová chromatografie; mykotoxiny; Swine; z-score; Zea mays; zvířata; Humans; Tandem Mass Spectrometry; chromatografie kapalinová; prasata; tandemová hmotnostní spektrometrie; Chromatography, Liquid; complex feed; certified reference material; lidé; Animals